2022
DOI: 10.2174/1874467214666210420115431
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin Antagonists: Exploring New Avenues to Trigger Old Drugs in Alleviating Glioblastoma Multiforme

Abstract: Background: Glioblastoma multiforme is one of the most heterogenous primary brain tumor with high mortality. Nevertheless, of the current therapeutic approaches, survival rate remains poor with 12 to 15 months following preliminary diagnosis, this warrants the need for effective treatment modality. Wnt/β-catenin pathway is presumably the most noteworthy pathway up-regulated in almost 80% GBM cases contributing to tumor-initiation, progression and survival. Therefore, therapeutic strategies targeting key compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 194 publications
0
11
0
Order By: Relevance
“…However, the regulation of ROS is often known to maintain cellular stability and enhance tumor progression by modulating various proliferative pathways such as PI3K/AKT/mTOR pathway, MAPK pathway and Wnt signalling pathway (Precilla et al, 2021). Among these, the PI3K/AKT/mTOR pathway has been reported to be aberrantly activated in almost 80% glioma cases (Cancer Genome Atlas Research Network, 2008;Cheng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the regulation of ROS is often known to maintain cellular stability and enhance tumor progression by modulating various proliferative pathways such as PI3K/AKT/mTOR pathway, MAPK pathway and Wnt signalling pathway (Precilla et al, 2021). Among these, the PI3K/AKT/mTOR pathway has been reported to be aberrantly activated in almost 80% glioma cases (Cancer Genome Atlas Research Network, 2008;Cheng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In highly proliferative tumors such as glioma, the increased metabolic rates lead to the accumulation of higher concentration of free radicals, leading to an increase in ROS levels (Olivier et al, 2020). However, the regulation of ROS is often known to maintain cellular stability and enhance tumor progression by modulating various proliferative pathways such as PI3K/AKT/mTOR pathway, MAPK pathway and Wnt signalling pathway (Precilla et al, 2021). Among these, the PI3K/AKT/mTOR pathway has been reported to be aberrantly activated in almost 80% glioma cases (Cancer Genome Atlas Research Network, 2008; Cheng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 3, 2022. ; https://doi.org/10.1101/2022.12.02.518940 doi: bioRxiv preprint Interestingly, from our preliminary in silico analysis, we had observed that all the four drugs namely, TMZ, CHL, NAR and PGL had depicted a profound interaction with two major receptors of WNT/β-catenin signaling pathway namely, Frizzled (FZD) and the co-receptor, the low-density lipoprotein receptor-related protein/alpha 2-macroglobulin receptors (LRP5/6) (Precilla et al 2021). On grounds of this in silico finding, we analysed the regulation of WNT/β-catenin pathway by this quadruple-drug cocktail (TCNP) with major focus on the expression signatures of the main components namely, EGFR, β-catenin, c-myc, c-jun and ERK-2.…”
Section: Green Arrowheads)mentioning
confidence: 99%
“…However, besides observation of their pathological effect, studies that shed molecular insights on the mechanism of action of the drugs would lay a profound background for further investigations on this quadruple-drug combination (TCNP). This is because, being a tumor with complex heterogeneity, GB is characterized by aberrant activation of major signal transduction pathways such as PI3K/AKT/mTOR, RAS/RAF/MAPK, Notch, Hedgehog and WNT signalling pathways which contributes to glioma proliferation (Jeuken et al 2007; Fan and Weiss 2010; Stockhausen et al 2010; Liu et al 2011, 2014; Precilla et al 2021; Daisy Precilla et al 2022). Among these, the WNT/ β-catenin signalling pathway is of paramount importance in gliomagenesis, as it enables GB cells to recapitulate the embryonic processes, thereby promoting glioma growth, progression and therapeutic resistance (Latour et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation